Computational Prediction and Structural Analysis of α-Hairpinins, a Ubiquitous Family of Antimicrobial Peptides, Using the Cysmotif Searcher Pipeline - Anna A. Slavokhotova; Andrey A. Shelenkov; Eugene A. Rogozhin (Antibiotics)
Background: α-Hairpinins are a family of antimicrobial peptides, promising antimicrobial agents, which includes only 12 currently revealed members with proven activity, although their real number is supposed to be much higher. α-Hairpinins are short peptides containing four cysteine residues arranged in a specific Cys-motif. These antimicrobial peptides (AMPs) have a characteristic helix−loop−helix structure with two disulfide bonds. Isolation of α-hairpinins by biochemical methods is cost- and labor-consuming, thus requiring reliable preliminary in silico prediction. Methods: In this study, we developed a special algorithm for the prediction of putative α-hairpinins on the basis of characteristic motifs with four (4C) and six (6C) cysteines deduced from translated plant transcriptome sequences. We integrated this algorithm into the Cysmotif searcher pipeline and then analyzed all transcriptomes available from the One Thousand Plant Transcriptomes project. Results: We predicted more than 2000 putative α-hairpinins belonging to various plant sources including algae, mosses, ferns, and true flowering plants. These data make α-hairpinins one of the ubiquitous antimicrobial peptides, being widespread among various plants. The largest numbers of α-hairpinins were revealed in the Papaveraceae family and in Papaver somniferum in particular. Conclusions: By analyzing the primary structure of α-hairpinins, we concluded that more predicted peptides with the 6C motif are likely to have potent antimicrobial activity in comparison to the ones possessing 4C motifs. In addition, we found 30 α-hairpinin precursors containing from two to eight Cys-rich modules. A striking similarity between some α-hairpinin modules belonging to diverse plants was revealed. These data allowed us to assume that the evolution of α-hairpinin precursors possibly involved changing the number of Cys-rich modules, leading to some missing middle and C-terminal modules, in particular.